Passenger Satisfaction towards Indian Railway in Kerala with Special Reference to Aluva Junction - Girish. S, Parvathy Asokan (International Journal of Advanced Science and Technology, 2020)
Transport is a vital infrastructure within the economy of India. It assumes a bigger role in developing countries since all the sectors of the event area unit closely dependent upon the existence of acceptable transportation network. The study is being conducted in Aluva town. Supply knowledge of information is adopted on primary data assortment among one hundred respondents. Aluva junction is regarded as the nerve centre which connects the highland districts to the rest of the state. And it is also railway station which has the higher rate of passengers round the clock. Overall study deals concerning the level of satisfaction of passengers in the basic, modern and outstation amenities offered by Indian railways. The study also points on the insights to develop and improve the standard of services to satisfy the travelers to travel in train. The study mainly focuses on the association between the demographic factors and the level of satisfaction of passengers.